Uses of Pursed Lips Breathing and Chest Physiotherapy to Improve Oxygenation Status in Pneumonia Patients - Utami, Theresia Febriana Christi Tyas; Kismiyati, Kismiyati; Nasrah, Nasrah (Indonesian Journal of Global Health Research, 2025)
Pneumonia is an inflamed lung infection. The disease is becoming one of the major problems in global public health due to its significant impact on morbidity and mortality. One of the non-pharmacological therapies that can help in handling pneumonia cases is Pursed Lips Breathing Breathing, this technique helps improve lung function, and Chest Physiotherapy helps in removing mucus trapped in the lungs. Objective to analyze the intervention of Pursed Lips Breathing and Chest Physiotherapy therapy to improve airway proficiency in the Emergency Installation Room of Abepura Hospital. This research uses a case study method, data collection is carried out through anamnesis to find out the patient's identity and complaints, observation and physical examination when conducting nursing assessments on patients. The subjects in this study were one Pneumonia patient with respiratory disorders and experienced an increase in respiratory rate (RR) and oxygen saturation. Pursed Lips Breathing and Chest Physiotherapy therapy was administered 1 time during treatment in the emergency room. From this case study, it was found that there was a decrease in respiratory rate (RR) and an increase in pulse oxygen saturation (SpO2), as well as airway proficiency with a decrease in sputum production. The application of innovative interventions needs to be carried out in the emergency room so that patients can control breathing when shortness of breath and when a restrained cough occurs. This intervention showed an improvement in the oxygenation status and airway competence of patients when given Pursed Lips Breathing and Chest Physiotherapy therapy.